IR luminescence of ZnSe-based scintillators - Vakulenko, O.V.; Kravchenko, V.M. (Functional Materials, 2004)
The work is aimed at the nature elucidation of IR photoluminescence (PL) bands with peaks at 1.3 and 1.6 eV (970 and 790 nm, respectively) in ZnSe and ZnSe(Te) crystals. Experimental studies of the PL of additionally purified crystals as well as calculations based on the charge carrier statistics in semiconductors with multicharge centers have shown that the IR PL is due to multicharge intrinsic point defects. The 1.3 eV IR band is attributed to intracenter transitions between excited and ground states of singly ionized selenium vacancies, which are double donors, whereas the 1.6 eV one, to radiative transitions of electrons from singly ionized Se vacancies to the acceptor level of the [ VznTese] complex.